Critical Endothelial Regulation by LRP5 during Retinal Vascular Development - Huang, Wei (PLoS One, 2016)
Vascular abnormalities in the eye are the leading cause of many forms of inherited and acquired human blindness. Loss-of-function mutations in the Wnt-binding co-receptor LRP5 leads to aberrant ocular vascularization and loss of vision in genetic disorders such as osteoporosis-pseudoglioma syndrome. The canonical Wnt-β-catenin pathway is known to regulate retinal vascular development. However, it is unclear what precise role LPR5 plays in this process. Here, we show that loss of LRP5 function in mice causes retinal hypovascularization during development as well as retinal neovascularization in adulthood with disorganized and leaky vessels. Using a highly specific Flk1-Cre(Breier) line for vascular endothelial cells, together with several genetic models, we demonstrate that loss of endothelium-derived LRP5 recapitulates the retinal vascular defects in Lrp5(-/-) mice. In addition, restoring LRP5 function only in endothelial cells in Lrp5(-/-) mice rescues their retinal vascular abnormalities. Furthermore, we show that retinal vascularization is regulated by LRP5 in a dosage dependent manner and does not depend on LRP6. Our study provides the first direct evidence that endothelium-derived LRP5 is both necessary and sufficient to mediate its critical role in the development and maintenance of retinal vasculature.